ESG Performance and Firm Value: Evidence from Agribusiness Companies Listed on Indonesia Stock Exchange - Sudarsono (Yayasan Darussalam Bengkulu, 2026)
ABSTRACT. This study investigates the relationship between Environmental, Social, and Governance (ESG) performance and firm value among agribusiness companies listed on the Indonesia Stock Exchange (IDX) over the period 2019–2023. Drawing on Stakeholder Theory, Agency Theory, and Signaling Theory, we hypothesize that ESG performance both in aggregate and across individual pillars positively influences firm value, and that this relationship is amplified by firm-level profitability. Using a balanced panel of 90 firm-year observations across 18 listed agribusiness companies, we employ Fixed Effects panel regression with cluster-robust standard errors and Moderated Regression Analysis (MRA) to test five hypotheses. The results confirm that aggregate ESG performance is positively and significantly associated with Tobin's Q (β = 0.018, p < 0.01). Decomposing ESG into its constituent pillars reveals that Governance exerts the strongest valuation effect (β = 0.021, p < 0.01), followed by Social (β = 0.014, p < 0.05) and Environmental performance (β = 0.011, p < 0.05). Furthermore, profitability significantly moderates the ESG–firm value relationship (β = 0.004, p < 0.05), indicating that financially stronger firms generate larger valuation premiums from equivalent ESG commitments. Findings are robust to alternative firm value proxies, lagged ESG specifications, and restricted high-disclosure subsamples. This study contributes rare sector-specific evidence from an emerging market context and offers actionable implications for corporate managers, ESG investors, and regulators seeking to strengthen sustainability frameworks within the Indonesian agribusiness industry